Efektivitas Quadriceps Setting Exercise (QSE) Dalam Meningkatkan Kemampuan Fungsional Pada Pasien Osteoartritis Lutut Genu Bilateral - Aditya Denny Pratama (Jurnal Ilmiah Fisioterapi, 2021)
Background: Osteoarthritis (OA) is a long-term chronic disease characterized by damage to joint cartilage which causes friction between bones, causing stiffness, pain, and restriction of movement in the knee joint. While osteoarthritis genu is a degenerative joint disease associated with cartilage damage in the knee joint. Quadriceps Setting Exercise (QSE) exercise therapy generally provides benefits in reducing complaints which are thought to be able to improve the patient's functional ability to perform activities optimally. The aim of this study was to determine the effectiveness of the Quadriceps Setting Exercise (QSE) method in cases of knee osteoarthritis. Methods: Single case study, giving physiotherapy intervention to a 77-year-old woman with a diagnosis of bilateral genu knee OA. QSE was given for 2 weeks with 4 evaluations. Assessment of muscle strength using MMT. Results: There is an increase in MMT from 4 to 5 which is associated with the WOMAC score from 37 to 27, which indicates that there is an increase in the functional ability of the patient Conclusion: This study shows that the Quadriceps Setting Exercise (QSE) method of exercise can improve functional ability in osteoarthritis knees were measured using the WOMAC parameter.